KOMPETENSI SOSIAL GURU IPA DI MADRASAH IBTIDAIYAH SWASTA ANNUR ISLAMIC FULLDAY SCHOOL TAHUN AJARAN 2020-2021 - Ranisa Sagita; Nazar Ikhwan; Rohanis Luthfiyyah Rahma; Luthfi Hakim (Academy of Education Journal, 2022)
Social competence is the ability of teachers to communicate and interact effectively and efficiently with students, fellow teachers, parents/guardians of students and the surrounding community. A teacher must try to develop communication both in the school environment and in the community. This research uses naturalistic qualitative research, which aims to make jokes in a systematic, accurate and accurate way about the facts or encountered in the field. The result of this research is that science teachers have not fully implemented social competence indicators. The indicators that have not been fully implemented are building effective communication with parents of students, and science teachers have not communicated with their own professional community and other professions orally and in writing or in other forms